High-strength low-temperature co-fired ceramic material and preparation method thereof

Through the close combination of the modified Al2O3 thermally conductive slurry with CaCO3-SiO2-Bi2O3 glass matrix, the problem of insufficient mechanical strength of LTCC materials is solved, and the preparation of ceramic materials with high strength, excellent thermal conductivity and low thermal expansion coefficient is achieved.

CN119569425AActive Publication Date: 2025-03-07ANHUI IND TECH INNOVATION RES INST LUAN INST
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410966347.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-18
Publication Date
2025-03-07
Estimated Expiration
2044-07-18

AI Technical Summary

Technical Problem

The mechanical strength of existing low-temperature co-fired ceramic (LTCC) materials is insufficient, which affects their reliability and performance in electronic components.

Method used

By ball milling the Al2O3 powder in an ethanol medium containing KOH, the surface defects are enhanced, and then closely bonded to the CaO-SiO2-Bi2O3 glass matrix to form a modified Al2O3 thermally conductive slurry. Subsequently, the modified Al2O3 thermally conductive slurry is mixed with the CaCO3-SiO2-Bi2O3 mixed slurry, and after melting, water-cooling quenching and ball milling, a high-strength low-temperature co-fired ceramic material is obtained.

Benefits of technology

It realizes the high strength, excellent thermal conductivity, low thermal expansion coefficient and excellent dielectric properties of LTCC materials, and is suitable for packaging scenarios with high strength requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569425A_ABST
    Figure CN119569425A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of low-temperature co-fired ceramic materials, and particularly relates to a high-strength low-temperature co-fired ceramic material and a preparation method thereof. The preparation method of the low-temperature co-fired ceramic material comprises the following steps: carrying out ball milling on Al2O3 powder in a KOH-containing ethanol medium, dropwise adding TEOS, continuously carrying out ball milling, adding a small amount of CaCO3 powder, and carrying out ball milling to obtain modified Al2O3 heat-conducting slurry; then weighing CaCO3, SiO2 and Bi2O3 raw materials, carrying out uniform ball milling, pouring into the modified Al2O3 heat-conducting slurry, carrying out uniform ball milling for a short time, then carrying out drying, then carrying out melting and water-cooling quenching in a high-temperature furnace, carrying out ball milling and crushing on the quenched glass frit, then adding a solvent, a dispersant, an adhesive, a plasticizer and a homogenizing agent, carrying out mixing and ball milling, carrying out tape casting on the obtained slurry to form a green tape, and carrying out heat treatment on the green tape to obtain the heat-conducting ceramic tape. And after overlying and molding, degumming and sintering in a high-temperature furnace to obtain the LTCC base material. The prepared low-temperature co-fired ceramic material has relatively high strength, excellent heat conductivity and low thermal expansion coefficient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of low temperature co-fired ceramic materials and preparation thereof, and in particular relates to a LTCC material and a preparation method thereof. Background Art

[0002] Low temperature co-fired ceramic (LTCC) technology is an excellent packaging technology for achieving integration and miniaturization of electronic components. LTCC technology can be used to assemble circuits, inductors, electronic devices, microwave devices, etc., to make high-density circuits that do not interfere with each other in three-dimensional space, or to make three-dimensional circuit substrates with built-in passive components. It provides a good solution for the integration, miniaturization and high reliability of electronic components, and has broad application prospects in the fields of communications, energy, aerospace, military industry, etc.

[0003] In the application of LTCC integrated devices, in order to improve the safety and reliability of electronic components, higher requirements are put forward for the thermal expansion coefficient and mechanical strength of LTCC materials. At present, in order to match the connection reliability between surface mount chips and LTCC substrate materials, the thermal expansion coefficients of various LTCC substrate materials are regulated at about 3.5ppm / ℃, which is equivalent to the thermal expansion coefficient of silicon-based chips. In addition, the LTCC substrate material has a certain strength, which is also a guarantee for the reliable operation of LTCC integrated devices. In some application scenarios, in order to ensure the reliability of LTCC substrate integrated devices, it is even necessary to install high-strength protective components such as metal to ensure the safety and reliability of internal LTCC substrate integrated devices. Therefore, improving the mechanical strength of LTCC materials is also a very meaningful research and development direction. LTCC materials with Al2O3 ceramic thermal conductive matrix are one of the mainstream LTCC materials. When co-fired at low temperature, the amount of Al2O3 ceramic dissolved in glass is very small, which will inhibit the crystallization of glass and affect the strength of the substrate. Insufficient wettability and bonding between glass and Al2O3 will also affect the dispersion of Al2O3 ceramics in the glass phase, inhibit the crystallization of calcium feldspar in the glass phase, and is not conducive to improving the strength of LTCC materials. Summary of the invention

[0004] In order to solve the technical problems existing in the background technology, one of the purposes of the present invention is to provide a high-strength low-temperature co-fired ceramic material and a preparation method thereof. The preparation method is simple and controllable, and the Al2O3 thermal conductive powder is tightly combined with the CaO-SiO2-Bi2O3 glass matrix. The obtained LTCC material has high strength, excellent thermal conductivity, low thermal expansion coefficient and excellent dielectric properties.

[0005] To achieve the above object, the present invention adopts the following technical solution: a method for preparing a high-strength low-temperature co-fired ceramic material, comprising the following steps:

[0006] (1) Weigh 100 parts by mass of Al2O3 powder, 100 parts by mass of ethanol and 1-5 parts by mass of KOH, mix and ball-mill for 2-4 hours; then drop 0.1-2 parts by mass of TEOS, ball-mill for 2-4 hours, then add 1-3 parts by mass of CaCO3 powder, and continue ball-milling for 2-4 hours to obtain a ball-milled modified Al2O3 thermal conductive slurry;

[0007] (2) weighing 20-30 parts by weight of CaCO3 powder, 19-26 parts by weight of SiO2 powder, 16-24 parts by weight of Bi2O3 and 60-100 parts by weight of ethanol, mixing and ball milling for 2-4 hours to obtain a CaCO3-SiO2-Bi2O3 mixed slurry;

[0008] (3) mixing the Al2O3 thermal conductive slurry modified by ball milling in step (1) and the CaCO3-SiO2-Bi2O3 mixed slurry in step (2), ball milling for 10-30 minutes, drying at 60°C, and then melting at 1200°C for 2-4 hours, and quenching by water cooling to obtain a quenched glass frit;

[0009] (4) ball milling the quenched glass frit in an ethanol medium for 12-20 hours and drying, adding 150-200 parts by weight of an azeotropic solvent and 3.2-4 parts by weight of a dispersant to the obtained powder, and then ball milling for 8-12 hours to obtain a uniformly dispersed suspension;

[0010] (5) adding 8-9 parts by weight of a binder, 11.4-12.85 parts by weight of a plasticizer, and 0.01-0.03 parts by weight of a homogenizer, cyclohexanone, to the suspension, and ball milling again for 8-12 hours to obtain a stable and uniform slurry;

[0011] (6) The slurry is vacuum degassed and then tape-casted, and after drying, the LTCC green tape material is obtained. The green tape is then cut and debonded at 300-650°C for 1-3 hours, and then sintered at 750-950°C for 1-3 hours to obtain a high-strength low-temperature co-fired ceramic material.

[0012] Further improvement of the preparation method of high-strength low-temperature co-fired ceramic materials:

[0013] Preferably, the rotation speed of the ball mill is controlled at 200-400 r / min.

[0014] Preferably, in step (4), the amount of the ethanol medium is 3-8 times the mass of the glass frit.

[0015] Preferably, in step (4), the azeotropic solvent is a mixed solvent of ethanol and xylene in a mass ratio of 1:(0.5-1).

[0016] Preferably, in step (4), the dispersant is one or a combination of two or more of castor oil, fish oil, phosphate ester, and triethanolamine.

[0017] Preferably, in step (7), the binder is one or a combination of two or more of polyvinyl alcohol, polyvinyl butyral, polyvinyl pyrrolidone, polymethyl methacrylate, and polyvinyl chloride.

[0018] Preferably, in step (7), the plasticizer is one or a combination of two or more of dibutyl phthalate, dimethyl phthalate, dioctyl phthalate, butyl benzyl phthalate, and polyethylene glycol.

[0019] Preferably, in step (7), the homogenizing agent is cyclohexane or cyclohexanone.

[0020] Preferably, in step (7), the mass ratio of the binder to the plasticizer is 0.7:1.

[0021] A second object of the present invention is to provide a high-strength low-temperature co-fired ceramic material prepared by the method for preparing the high-strength low-temperature co-fired ceramic material described in any one of the above.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1) The present invention provides a method for preparing a high-strength low-temperature co-fired ceramic material. The low-temperature co-fired ceramic material firstly ball-mills Al2O3 powder in an ethanol medium containing KOH to improve the surface defects of the Al2O3 thermal conductive powder, then drips TEOS and continues ball-milling, and then adds a small amount of CaCO3 powder to ball-mill to obtain a modified Al2O3 thermal conductive slurry; then weighs CaCO3, SiO2 and Bi2O3 raw materials and ball-mills them evenly, promotes the glass phase to be more closely combined with the Al2O3 thermal conductive powder, helps Al2O3 to be better dispersed in the glass phase, and can effectively improve the mechanical properties of the LTCC material. Then, the mixed slurry after ball milling is poured into the modified Al2O3 thermal conductive slurry, ball-milled evenly for a short time, and then dried, and then melted in a high-temperature furnace, water-cooled quenched, the quenched glass frit is ball-milled and crushed, and then a solvent, a dispersant, an adhesive, a plasticizer and a homogenizer are added and mixed and ball-milled, and then the obtained slurry is cast into a green porcelain tape, which is laminated and formed, and then debinded and sintered in a high-temperature furnace to obtain a LTCC substrate.

[0024] 2) The flexural strength of the low-temperature co-fired ceramic material prepared by the present invention can reach up to 327Mpa, the thermal conductivity can be greater than 3.526W / (m·K), and the thermal expansion coefficient is 4.28-4.56ppm / ℃. It can be applied to packaging scenarios with high strength requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a scanning electron microscope photograph of the high-strength low-temperature co-fired ceramic material prepared by the present invention. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.

[0027] Example 1

[0028] This embodiment provides a method for preparing a high-strength low-temperature co-fired ceramic material, comprising the following steps:

[0029] (1) Weigh 100 parts by mass of Al2O3 powder, 100 parts by mass of ethanol and 1 part by mass of KOH, mix and ball-mill for 2 hours; then drop 0.5 parts by mass of TEOS, ball-mill for 2 hours, then add 1 part by mass of CaCO3 powder, and continue ball-milling for 2 hours to obtain a ball-milled modified Al2O3 thermal conductive slurry;

[0030] (2) Weighing 20 parts by mass of CaCO3 powder, 26 parts by mass of SiO2 powder, 24 parts by mass of Bi2O3 and 80 parts by mass of ethanol, mixing and ball milling for 2 hours to obtain a CaCO3-SiO2-Bi2O3 mixed slurry;

[0031] (3) mixing the Al2O3 thermal conductive slurry modified by ball milling in step (1) and the CaCO3-SiO2-Bi2O3 mixed slurry in step (2), ball milling for 10 minutes, drying by air blast at 60°C, and then melting at 1200°C for 2 hours, and quenching by water cooling to obtain a quenched glass frit;

[0032] (4) ball milling the quenched glass frit in 3 parts by mass of ethanol for 12 h and drying, adding 180 parts by mass of an azeotropic solvent (a mixed solvent of ethanol and xylene in a mass ratio of 1:1) and 3.6 parts by mass of a dispersant (castor oil) to the obtained powder, and then ball milling for 8 h to obtain a uniformly dispersed suspension;

[0033] (5) 9 parts by weight of a binder (polyvinyl butyral), 12.85 parts by weight of a plasticizer (butyl benzyl phthalate) and 0.02 parts by weight of a homogenizer (cyclohexanone) were added to the suspension and ball milled again for 8 h to obtain a stable and uniform slurry;

[0034] (6) The slurry is vacuum degassed and then tape-casted, and after drying, the LTCC green tape material is obtained. The green tape is then cut and debonded at 300°C for 3 hours and then sintered at 800°C for 2 hours to obtain a high-strength, low-temperature co-fired ceramic material.

[0035] Example 2

[0036] This embodiment provides a method for preparing a high-strength low-temperature co-fired ceramic material, comprising the following steps:

[0037] (1) Weigh 100 parts by mass of Al2O3 powder, 100 parts by mass of ethanol and 2 parts by mass of KOH, mix and ball-mill for 2 hours; then drop 2 parts by mass of TEOS, ball-mill for 2 hours, then add 3 parts by mass of CaCO3 powder, and continue ball-milling for 2 hours to obtain a ball-milled modified Al2O3 thermal conductive slurry;

[0038] (2) Weighing 21 parts by mass of CaCO3 powder, 19 parts by mass of SiO2 powder, 20 parts by mass of Bi2O3 and 60 parts by mass of ethanol, mixing and ball milling for 2 h to obtain a CaCO3-SiO2-Bi2O3 mixed slurry;

[0039] (3) mixing the Al2O3 thermal conductive slurry modified by ball milling in step (1) and the CaCO3-SiO2-Bi2O3 mixed slurry in step (2), ball milling for 20 minutes, drying by forced air at 60°C, and then melting at 1200°C for 2 hours, and quenching by water cooling to obtain a quenched glass frit;

[0040] (4) ball milling the quenched glass frit in 5 parts by mass of ethanol for 12 h and drying, adding 163 parts by mass of an azeotropic solvent (a mixed solvent of ethanol and xylene in a mass ratio of 1:1) and 3.2 parts by mass of a dispersant (castor oil) to the obtained powder, and then ball milling for 8 h to obtain a uniformly dispersed suspension;

[0041] (5) 8 parts by weight of a binder (polyvinyl butyral), 11.4 parts by weight of a plasticizer (butyl benzyl phthalate) and 0.02 parts by weight of a homogenizer (cyclohexanone) were added to the suspension and ball milled again for 8 h to obtain a stable and uniform slurry;

[0042] (6) The slurry is vacuum degassed and then tape-casted, and after drying, the LTCC green tape material is obtained. The green tape is then cut and debonded at 650°C for 1 hour and then sintered at 900°C for 2 hours to obtain a high-strength low-temperature co-fired ceramic material.

[0043] Example 3

[0044] This embodiment provides a method for preparing a high-strength low-temperature co-fired ceramic material, comprising the following steps:

[0045] (1) Weigh 100 parts by mass of Al2O3 powder, 100 parts by mass of ethanol and 5 parts by mass of KOH, mix and ball-mill for 4 hours; then drop 1 part by mass of TEOS, ball-mill for 4 hours, then add 2 parts by mass of CaCO3 powder, and continue ball-milling for 4 hours to obtain a ball-milled modified Al2O3 thermal conductive slurry;

[0046] (2) Weighing 30 parts by mass of CaCO3 powder, 22 parts by mass of SiO2 powder, 20 parts by mass of Bi2O3 and 70 parts by mass of ethanol, mixing and ball milling for 4 hours to obtain a CaCO3-SiO2-Bi2O3 mixed slurry;

[0047] (3) mixing the Al2O3 thermal conductive slurry modified by ball milling in step (1) and the CaCO3-SiO2-Bi2O3 mixed slurry in step (2), ball milling for 20 minutes, drying by forced air at 60°C, and then melting at 1200°C for 2 hours, and quenching by water cooling to obtain a quenched glass frit;

[0048] (4) ball milling the quenched glass frit in 5 parts by mass of ethanol for 12 h and drying, adding 170 parts by mass of an azeotropic solvent (a mixed solvent of ethanol and xylene in a mass ratio of 1:0.5) and 3.4 parts by mass of a dispersant (castor oil) to the obtained powder, and then ball milling for 8 h to obtain a uniformly dispersed suspension;

[0049] (5) 8.5 parts by weight of a binder (polyvinyl butyral), 12.1 parts by weight of a plasticizer (butyl benzyl phthalate) and 0.03 parts by weight of a homogenizer (cyclohexanone) were added to the suspension and ball milled again for 8 h to obtain a stable and uniform slurry;

[0050] (6) The slurry is vacuum degassed and then tape-casted, and after drying, the LTCC green tape material is obtained. The green tape is then cut, debonded at 600°C for 2 hours, and sintered at 850°C for 2 hours to obtain a high-strength, low-temperature co-fired ceramic material.

[0051] Example 4

[0052] This embodiment provides a method for preparing a high-strength low-temperature co-fired ceramic material, comprising the following steps:

[0053] (1) Weigh 100 parts by mass of Al2O3 powder, 100 parts by mass of ethanol and 2 parts by mass of KOH, mix and ball-mill for 2 hours; then drop 1 part by mass of TEOS, ball-mill for 2 hours, then add 1 part by mass of CaCO3 powder, and continue ball-milling for 2 hours to obtain a ball-milled modified Al2O3 thermal conductive slurry;

[0054] (2) Weighing 27 parts by mass of CaCO3 powder, 23 parts by mass of SiO2 powder, 16 parts by mass of Bi2O3 and 70 parts by mass of ethanol, mixing and ball milling for 2 hours to obtain a CaCO3-SiO2-Bi2O3 mixed slurry;

[0055] (3) mixing the Al2O3 thermal conductive slurry modified by ball milling in step (1) and the CaCO3-SiO2-Bi2O3 mixed slurry in step (2), ball milling for 30 minutes, drying by air blast at 60°C, and then melting at 1200°C for 2 hours, and quenching by water cooling to obtain a quenched glass frit;

[0056] (4) ball milling the quenched glass frit in 3 parts by mass of ethanol for 20 h and drying, adding 170 parts by mass of an azeotropic solvent (a mixed solvent of ethanol and xylene in a mass ratio of 1:1) and 3.4 parts by mass of a dispersant (castor oil) to the obtained powder, and then ball milling for 8 h to obtain a uniformly dispersed suspension;

[0057] (5) 8.5 parts by weight of a binder (polyvinyl butyral), 12.1 parts by weight of a plasticizer (butyl benzyl phthalate) and 0.03 parts by weight of a homogenizer (cyclohexanone) were added to the suspension and ball milled again for 8 h to obtain a stable and uniform slurry;

[0058] (6) The slurry is vacuum degassed and then tape-casted, and after drying, the LTCC green tape material is obtained. The green tape is then cut and debonded at 600°C for 2 hours and then sintered at 900°C for 1 hour to obtain a high-strength low-temperature co-fired ceramic material.

[0059] Example 5

[0060] This embodiment provides a method for preparing a high-strength low-temperature co-fired ceramic material, comprising the following steps:

[0061] (1) Weigh 100 parts by mass of Al2O3 powder, 100 parts by mass of ethanol and 1 part by mass of KOH, mix and ball-mill for 2 hours; then drop 1 part by mass of TEOS, ball-mill for 2 hours, then add 1 part by mass of CaCO3 powder, and continue ball-milling for 2 hours to obtain a ball-milled modified Al2O3 thermal conductive slurry;

[0062] (2) Weigh 30 parts by mass of CaCO3 powder, 26 parts by mass of SiO2 powder, 24 parts by mass of Bi2O3 and 100 parts by mass of ethanol, mix and ball-mill for 2 h to obtain a CaCO3-SiO2-Bi2O3 mixed slurry;

[0063] (3) mixing the Al2O3 thermal conductive slurry modified by ball milling in step (1) and the CaCO3-SiO2-Bi2O3 mixed slurry in step (2), ball milling for 10 minutes, drying by air blast at 60°C, and then melting at 1200°C for 2 hours, and quenching by water cooling to obtain a quenched glass frit;

[0064] (4) ball milling the quenched glass frit in 3 parts by mass of ethanol for 12 h and drying, adding 180 parts by mass of an azeotropic solvent (a mixed solvent of ethanol and xylene in a mass ratio of 1:1) and 3.6 parts by mass of a dispersant (castor oil) to the obtained powder, and then ball milling for 8 h to obtain a uniformly dispersed suspension;

[0065] (5) 9 parts by weight of a binder (polyvinyl butyral), 12.85 parts by weight of a plasticizer (butyl benzyl phthalate) and 0.02 parts by weight of a homogenizer (cyclohexanone) were added to the suspension and ball milled again for 8 h to obtain a stable and uniform slurry;

[0066] (6) The slurry is vacuum degassed and then tape-casted, and after drying, the LTCC green tape material is obtained. The green tape is then cut and debonded at 620°C for 2 hours and then sintered at 800°C for 1.5 hours to obtain a high-strength low-temperature co-fired ceramic material.

[0067] Figure 1 is a scanning electron microscope photograph of the high-strength low-temperature co-fired ceramic material obtained in Example 1; Figure 1 It can be seen that there are small nanoparticles anchored on the surface of alumina, with a size of about 10-50nm, and the alumina is wrapped by the glass phase, and the glass phase and the alumina ceramic phase are in close contact.

[0068] The test results of thermal conductivity, thermal expansion coefficient and flexural strength of the high-strength low-temperature co-fired ceramic materials prepared in Examples 1-5 are shown in Table 1 below:

[0069] Table 1

[0070]

[0071]

[0072] The test results show that after Al2O3 powder is ball-milled in an alkaline solution, it is combined with in-situ riveted silica nanoparticles and a small amount of calcium carbonate nanopowder is added to co-ball-mill to obtain a modified Al2O3 thermal conductive slurry, which is then ball-milled with the glass powder raw material CaCO3-SiO2-Bi2O3 mixed slurry and sintered, and then ball-milled into co-fired ceramic powder, and then a casting aid is added to obtain a green ceramic tape. The flexural strength of the sintered ceramic sample is significantly improved, up to 327Mpa, while the thermal conductivity can be maintained above 3.526W / (m·K), and the thermal expansion coefficient is 4.28-4.56ppm / ℃. High flexural strength can broaden the packaging application of this low-temperature co-fired ceramic material in the context of high-strength requirements.

[0073] Those skilled in the art should understand that the above are only some specific embodiments of the present invention, rather than all embodiments. It should be noted that for those of ordinary skill in the art, many modifications and improvements can be made, and all modifications or improvements that do not exceed the scope of protection of the present invention should be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a high-strength low-temperature co-fired ceramic material, characterized in that: The following steps are involved: (1) Weigh 100 parts by mass of Al2O3 powder, 100 parts by mass of ethanol and 1-5 parts by mass of KOH, mix and ball-mill for 2-4 hours; then drop 0.1-2 parts by mass of TEOS, ball-mill for 2-4 hours, then add 1-3 parts by mass of CaCO3 powder, and continue ball-milling for 2-4 hours to obtain a ball-milled modified Al2O3 thermal conductive slurry; (2) weighing 20-30 parts by weight of CaCO3 powder, 19-26 parts by weight of SiO2 powder, 16-24 parts by weight of Bi2O3 and 60-100 parts by weight of ethanol, mixing and ball milling for 2-4 hours to obtain a CaCO3-SiO2-Bi2O3 mixed slurry; (3) mixing the Al2O3 thermal conductive slurry modified by ball milling in step (1) and the CaCO3-SiO2-Bi2O3 mixed slurry in step (2), ball milling for 10-30 minutes, drying at 60°C, and then melting at 1200°C for 2-4 hours, and quenching by water cooling to obtain a quenched glass frit; (4) ball milling the quenched glass frit in an ethanol medium for 12-20 hours and drying, adding 150-200 parts by weight of an azeotropic solvent and 3.2-4 parts by weight of a dispersant to the obtained powder, and then ball milling for 8-12 hours to obtain a uniformly dispersed suspension; (5) adding 8-9 parts by weight of a binder, 11.4-12.85 parts by weight of a plasticizer, and 0.01-0.03 parts by weight of a homogenizer, cyclohexanone, to the suspension, and ball milling again for 8-12 hours to obtain a stable and uniform slurry; (6) The slurry is vacuum degassed and then tape-casted, and after drying, the LTCC green tape material is obtained. The green tape is then cut and debonded at 300-650°C for 1-3 hours, and then sintered at 750-950°C for 1-3 hours to obtain a high-strength low-temperature co-fired ceramic material.

2. The method for preparing a high-strength low-temperature co-fired ceramic material according to claim 1, characterized in that: The rotation speed of the ball mill is controlled at 200-400r / min.

3. The method for preparing a high-strength low-temperature co-fired ceramic material according to claim 1, characterized in that: In the step (4), the amount of the ethanol medium is 3-8 times the mass of the glass frit.

4. The method for preparing a high-strength low-temperature co-fired ceramic material according to claim 1, characterized in that: In the step (4), the azeotropic solvent is a mixed solvent of ethanol and xylene, with a mass ratio of 1:(0.5-1).

5. The method for preparing a high-strength low-temperature co-fired ceramic material according to claim 1, characterized in that: In the step (4), the dispersant is one or a combination of two or more of castor oil, fish oil, phosphate ester, and triethanolamine.

6. The method for preparing a high-strength low-temperature co-fired ceramic material according to claim 1, characterized in that: In the step (7), the binder is one or a combination of two or more of polyvinyl alcohol, polyvinyl butyral, polyvinyl pyrrolidone, polymethyl methacrylate, and polyvinyl chloride.

7. The method for preparing a high-strength low-temperature co-fired ceramic material according to claim 1, characterized in that: In the step (7), the plasticizer is one or a combination of two or more of dibutyl phthalate, dimethyl phthalate, dioctyl phthalate, butyl benzyl phthalate, and polyethylene glycol.

8. The method for preparing a high-strength low-temperature co-fired ceramic material according to claim 1, characterized in that: In the step (7), the homogenizing agent is cyclohexane or cyclohexanone.

9. The method for preparing a high-strength low-temperature co-fired ceramic material according to claim 1, 7 or 8, characterized in that: In the step (7), the mass ratio of the binder to the plasticizer is 0.7:

1.

10. A high-strength low-temperature co-fired ceramic material prepared by the method for preparing a high-strength low-temperature co-fired ceramic material according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Low-temperature co-fired ceramic substrate material and preparation method thereof

    CN101717245A

  • Preparation method of low-temperature co-fired ceramic material composite substrate

    CN109467415A

  • Heat-conducting low-temperature co-fired ceramic material and preparation method thereof

    CN110683837A

  • Synthesis of glass-ceramic composite for LTCC(LowTemperature Co-firing Ceramic)

    KR1020050078785A

  • Low temperature fired ceramics

    US4621066A